Síndrome de Tako-Tsubo. A propósito de un caso. Tako-Tsubo syndrome. With regard to a case - Joel Brooks Tamayo; Tomás C. Méndez Peralta; Abel Y. Leyva Quert; Javier Almeida Gómez; Orlando Alvarez Toledo; Pedro Conde Pérez (ECIMED, 2010)
We present a patient with a history of hypercholesterolemia referred due to sudden appearance of an intense and oppresive pain in the anterior region of the thorax irradiating to the back accompanied of a convex ST segment elevation in the anterior leads. An echocardiogram and ventriculography were carried out confirming the presence of apical akinesia with a systolic function slightly depressed. The coronary angiography did not show angiographic lesions. We conclude this patient suffered a Tako-Tsubo syndrome fulfilling the diagnostic criteria proposed by the Mayo Clinic.